Escolha de genitores em melão amarelo: análise dialélica e estimativa de m + a’ - Ferreira, karmita Thainá Correia (Universidade Federal Rural do Semi-Árido, 2020)
One of the reasons for the success of the melon crop must be the use of improved seeds, especially hybrids. The diallel crossbreeding systems show the best hybrids and help in choosing parents to be used in breeding programs. The identification of promising changes, derived from superior hybrids, is a strategy to increase the efficiency of melon improvement programs. Among the procedures that help in choosing the most promising variations and lines, it is highlighted the estimation of m + a 'd. Therefore, the aim of this study was to evaluate the performance of commercial melon hybrids and their hybrid combinations, using two models of diallel analysis and to estimate a contribution of locals in heterozygosis (d) and in homozygosis (m + a ') of characters in commercial yellow melon hybrids. Manual crosses were performed between seven simple commercial hybrids, forming twenty-one hybrid combination. The trials were conducted in randomized blocks with three repetitions, in the years 2017 and 2018, in the cities of Baraúna and Mossoró, in Rio Grande do Norte. For the first experiment, twenty-eight controls (7 hybrids + 21 hybrid combinations) were considered. A dialogical analysis considered the Griffing fixed model and the BLUP random model. The second experiment considered seven commercial F1 hybrids and their self-fertilizing F2, totaling fourteen tests to evaluate the estimate of m + a and d. The number of fruits, average fruit weight, reproduction, pulp thickness, pulp firmness and soluble solids content were taxed. There were genetic and non-additive effects on character control. Parents A4 and A6 showed greater general combining ability for most characters. The hybrids A4 x A7 and A1 x A6 present the best performances of the specific combining ability. The characters reduce the greater contribution of loco in homozygosis, this contribution being more than 90% for thickness and firmness of the pulp, and high soluble. The variation potential for extracting strains can be assessed by detecting m + a 'd
Keywords: Cucumis melo L.,; Melhoramento; Locos; Homozigose; Heterozigose; Cucumis melo L.; Breeding; Loci; Homozygosis; Heterozygosis; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA